Diagnosis and natural course of allergy to cooked potatoes in children - De Swert, L.F.A; Cadot, P; Ceuppens, J.L (Allergy, 2007)
Allergy to heat stable potato proteins can cause severe allergic disease in children. To study diagnostic criteria for allergy to cooked potatoes and to describe its clinical characteristics and natural history. Thirty-six children, aged 4-36 months, with atopic symptoms and having a positive potato-CAP and/or skin prick test (SPT) were included. Potato allergy was documented by means of provocation, or elimination and reintroduction or an unequivocal clinical history. Potato-CAP and SPT with a commercial extract were evaluated for diagnostic performance. Presenting symptoms in children with proven potato allergy (n = 17) were eczema (16 of 17), gastrointestinal complaints (eight of 17), urticaria and/or angioedema (five of 17), wheezing/rhinitis (three of 17) and anaphylaxis (two of 17). Fifteen children had previously diagnosed cow's milk protein allergy and were egg-sensitized. Potato-CAP at cut-off >2 kU/l provided a 100% sensitivity and a 62.5% specificity for diagnosis of potato allergy, while a SPT score >= 3 had a 100% sensitivity and a score >= 4 had a 100% specificity. Tolerance to cooked potato was achieved in 80% of subjects at age 16-102 months. Of 12 subjects having reached the age of 3 years during the study, 10 were re-evaluated at age 3-6 years: seven of 10 subjects had developed clinical pollen allergy, compared with four of 18 atopic controls (P < 0.05). Potato-CAP and SPT at specific cut-off are valuable tools in the diagnosis of allergy to cooked potato. Most children with potato allergy develop tolerance at mean age of 4 years. Allergy to cooked potatoes is a risk factor for the development of pollen allergy.